Electromagnetic Radio Receiver : A Design For Receiving Jupiter Signal - Abhishek, R; Rukmangada, R.; Rachana, M.; Prabu, T. (2019 IEEE International Conference on Intelligent Techniques in Control, Optimization and Signal Processing (INCOS), 2019)
In this paper we present the technical details of electromagnetic radio signal receiver that we have designed to observe the radio burst signals from the planet Jupiter. The novelty in the work comes from a custom designed electrically small loop antenna, simple RC filters, off the shelf amplifiers and a low cost Software Defined Radio (SDR) based data recorder. The paper describes design details of the receiver, implementation and test results.